2021
DOI: 10.3389/fendo.2021.629831
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency, a Risk Factor of Thyroid Disorders in Reproductive-Age and Pregnant Women: A Systematic Review and Meta-Analysis

Abstract: BackgroundIron deficiency (ID) is concerned as the most common nutritional deficiency worldwide. The effects of ID on thyroid function and autoimmunity in pregnant women and reproductive-age women are controversial. The aim of the current study was to summarize the evidences and evaluate the relationship between ID and thyroid disorders.MethodsIn this systematic review and meta-analysis, studies published on the Cochrane, Embase, Medline, and PubMed databases by October 2020 were searched. A total of 636 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
(36 reference statements)
2
17
0
Order By: Relevance
“…The undersupply of certain macro- and micronutrients appears to be a crucial risk factor for thyroid dysfunction [ 10 13 , 15 , 32 ]. Iron deficiency is one of the most common deficiency symptoms worldwide, which may manifest not only as iron deficiency anemia, but also in the form of low ferritin levels, thus negatively affecting thyroid metabolism [ 12 , 13 , 32 ]. This mainly happens through reduced thyroid hormone synthesis by the heme-dependent enzyme thyroid peroxidase (TPO) [ 11 , 12 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The undersupply of certain macro- and micronutrients appears to be a crucial risk factor for thyroid dysfunction [ 10 13 , 15 , 32 ]. Iron deficiency is one of the most common deficiency symptoms worldwide, which may manifest not only as iron deficiency anemia, but also in the form of low ferritin levels, thus negatively affecting thyroid metabolism [ 12 , 13 , 32 ]. This mainly happens through reduced thyroid hormone synthesis by the heme-dependent enzyme thyroid peroxidase (TPO) [ 11 , 12 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dosimetric factors, deficiency symptoms of certain macro-and micronutrients may occur in the context of tumor-or treatment-related malnutrition, favoring the development of hypothyroidism [9]: Among these are iodine (important component of fT3 and fT4), iron (required for thyroid hormone formation) [9][10][11][12][13], selenium (regulation of the conversion of fT4 to fT3) [14], and amino acids (needed for the formation of free thyroid hormones) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Iron deficiency significantly increases the risk of positive TPOAb and both positive TPOAb and TgAb in women of reproductive age. This study indicates that it is necessary to monitor the nutritional status of iron in AIT [ 97 ].…”
Section: Micronutrients In Htmentioning
confidence: 99%
“…IDA deteriorates thyroid metabolism and retards the physical and mental development of both young and adult individuals. Based on several investigations, both ID and Anemia are interconnected with hypothyroidism which significantly increases serum TSH levels and decreases serum iron, serum ferritin, Free T4, transferrin, RBC count, and so on [14][15][16][17][18]. Ferritin is a universal protein that acts as an iron carrier, and serum ferritin level is negatively correlated with serum TSH levels [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies highly suggested the supplementation of vitamin D in case of hypothyroidism and Anemia, along with the high recommendation for the screening of the vitamin D deficiency in all hypothyroid patients [25,32]. It is practically required for monitoring iron nutritional status as it exaggerates thyroid disorders in reproductive age and pregnant women [14]. Thyroid dysfunctions must also be considered by physicians treating Anemia to ensure early detection and proper treatment [33].…”
Section: Introductionmentioning
confidence: 99%